Optimization of β-D-galactosidase rapid enzyme assay using Escherichia coli ATCC 8739 - Tu, Le Thi Anh; Le, Le Ba (Vietnam Journal of Biotechnology, 2016)
The bacterial enzyme, β-D-galactosidase, catalyzes the breakdown of the complex sugar lactose into its components - galactose and glucose- simple sugars. The glycolysis of lactose by β-D-galactosidase is a point of attack for studies of the biochemical problem in disaccharide utilization and the genetic basis of enzyme constitution β-D galactosidase. The aim of the present study was to focus on optimization of a rapid enumeration method based on the enzymatic hydrolysis of 4-methylumbelliferyl-β-D-galactoside (MUGal) for toxicity test using Escherichia coli (E. coli) ATCC 8739 as a model. This rapid assay is based on the assumption that β-D-galactosidase is one marker for E. coli ATCC 8739. The enzymatic activity of E. coli ATCC 8739 was measured in a 25-minute assay. The effects of pH, temperature, nutrition, and substrate concentrations on enzyme activity were investigated. The enzyme β-D-galactosidase was shown to be induced with the inducer isopropyl-beta-D-thiogalactopyranoside (IPTG). The high level of production of β-D-galactosidase was found at bacteria incubated in tryptic soy broth without dextrose with IPTG. The optimum pH and temperature for β-D-galactosidase activity of E. coli ATCC 8739 was found to be 6.8 and 44.5 oC, respectively. The enzyme activity detected increased when raising the concentrations of the substrate (MUGal). The good linear correlation between logarithms of enzyme activities and CFU showed following supported the use of this method for toxicity experiments. Enzymatic methods and reference plate counts were significantly correlated. This method is sensitive, simple to perform and can be used as an alternative for traditional methods in detecting cell viability